PERLINDUNGAN HUKUM HAK-HAK LAINNYA NON UPAH PEKERJA PASCA PUTUSAN MAHKAMAH KONSTITUSI NOMOR 67/PUU-XI/2013 - Arben di (Universitas Slamet Riyadi, 2018)
AbstractThis research has purposes of knowing the interpretation of the supplementary worker rights definition after Constitutional Court Decision Number 67/PUU/XI/2013. This research has also purposes of knowing the preventive legal protection of the supplementary worker rights after the Decision of Constitutional Court No. 67/PUU-XI/2013. The results of this research are, firstly, the supplementary rights of worker are classified into: (a) normative, meaning that the supplementary rights which are provided and regulated by acts, such as severance payment, gratuity and compensative payment. (b) non-normative rights, meaning other rights are provided and regulated by the parties in accordance with the agreement in the employment agreement or collective labor agreement. Secondly, there are already legal protection of supplementary non-salary rights in Decision of Constitutional Court No. 67/PUU-XI/2013 but they are not completely protective because the supplementary rights of the worker are not included in separatist creditor payment.AbstrakPenelitian ini bertujuan untuk mengetahui, penafsiran definisi hak-hak lainnya dari pekerja/buruh Pasca putusan Mahkamah konstitusi Nomor 67/PUUXI/2013. Penelitian ini juga untuk mengetahui, perlindungan hukum preventif terhadap hak-hak lainnya dari pekerja/buruh Pasca putusan Mahkamah konstitusi Nomor 67/PUUXI/2013. Hasil penelitian ini adalah pertama, hak-hak lainnya pekerja/buruh dibagi menjadi: (a). bersifat normatif, adalah hak-hak lain yang diberikan dan diatur oleh Undangundang, misalnya uang Pesangon, uang penghargaan masa kerja, uang penggantian hak dan (b). Hak hak lainnya yang tidak bersifat normatif, berarti diberikan dan diatur oleh para pihak menurut kesepakatan baik dalam Perjanjian Kerja (PK) atau Perjanjian Kerja Bersama (PKB). Kedua, perlindungan hukum hak-hak lainnya dari pekerja/buruh Nomor 67/PUU-XI/2013 sudah ada namun tidak sepenuhnya terlindungi, dikarenakan hak-hak non upah pekerja/buruh dikecualikan pembayarannya oleh kreditur Separatis.